Cinema no contexto escolar: por uma pedagogia da criação - Barbosa, Diogo José de Moraes Lopes (2018)
In this research, we made a study about the practice of cinema in the school context. Educational institutions already have a certain history in the teaching arts, however, cinema as an artistic language, is still rarely seen in them. Therefore, our research proposal was to investigate the possibilities of teaching cinema in the school, especially in a practical perspective, from a experience of creation by the students. That is why of the use of the concept, pedagogy of creation, a term proposed by Alain Bergala (2008), a scholar of the teaching of cinema in schools, which presupposes that the study of cinematographic art must come along with the exercise of creating. So, at the beginning of our research, to be possible the student could appropriate the processes of cinematographic creation, we searched for a broader concept of the object in question. It was fundamental to understand the importance and necessity of bringing cinema to the school curriculum in its various dimensions: work of art, mass media, educational instrument, object of entertainment. We should remember our contemporary society is immersed by the cinema, besides the others many forms of audiovisual present in our daily life. Beyond understanding the need to teach and learn cinema, it is fundamental to know the tools to reach such propositions. In this research, we will present some approaches and methodologies of teaching art, of teaching communication and of the pedagogy of cinema. Finally, with these methodologies, to answer our main question – how to teach / learn cinema in the school in a practical – we apply the diverse ideas and thoughts of the theorists studied in a course offered to students of the Municipal School Of Iputinga in Recife. It had an eminently practical character, where students had the opportunity to use film equipments and footage and were able to produce their own films. The results obtained in this experiment, at the same time that showed us interesting and enriching possibilities in classroom teaching practices, alerted us to some problems in the implementation of differentiated projects in our public educational systems. In spite of this, we conclude that not only is it possible, but it is necessary to teach cinema at school, above all, based on a pedagogy based on the creation, experimentation, realization of works and audiovisual projects by students.